VARIASI SUHU PEMANASAN BIJI KARET (Hevea brasiliensis) TERHADAP MUTU MINYAK GORENG MENGGUNAKAN ZEOLIT SEBAGAI ADSORBEN - Simarmata, Novalinda Herawati; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Rubber seed is not utilized optimally nowdays. One alternative to utilize the rubber seed is using it’s oil as cooking oil. This research was aimed to obtain optimal heating temperature variation on the cyanide acid content and the quality of cooking oil produced. This research was conducted by using Completely Randomized Design (CRD) experiment with five treatmens and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatmens in this research were P1 (70°C for 4 hours), P2 (temperature 80°C for 4 hours), P3 (temperature 90°C for 4 hours), P4 (100°C for 4 hours). The results of variance analysis show that the higher the heating temperature significantly decreased the average content of cyanide, acid value, density and moisture content but increased saponification value. Based on the results obtained, the best treatment in the rubber seed heating was P4 treatment (100°C for 4 hours) with cyanide acid content 1,42 ppm, acid value 1,38 mg KOH/g, saponification value 161,64 mg KOH/g, density 0,864 g/ml and moisture content 0,912 %.  Keywords: Heating temperature, rubber seed, cyanide acid, cooking oil.